Does a Saline Load Test Combined with Direct Compression to the Knee Increase Sensitivity in the Assessment of a Traumatic Open Knee Injury? - Phonglaohaphan, MD, Surasit; Iamsumang, MD, Chonlathan (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To determine whether a saline load test combined with direct compression to the knee increases sensitivity for the assessment of traumatic arthrotomy of the knee. Methods: A total of 40 patients scheduled for elective inpatient knee arthroscopy and total knee arthroplasty (TKA) were prospectively enrolled. A 7 to 8 ml stab wound for arthrotomy was performed at the inferolateral site of the knee for cases who would receive arthroscopy and at the inferomedial site for the TKA cases. Then, 50 ml of normal saline was injected into the knee joint while observing fluid leakage from the arthrotomy site. It was considered a positive saline load test if there was any leakage. If not, subsequent direct compression was applied to the knee. Any leakage incurred was considered a positive compression test. Results: The saline load test was positive in 13 out of 40 patients and additional 18 patients showed a positive compression test. The sensitivity of the saline load test was 32.5% while that of the compression test was 77.5%. Conclusion: Additional direct compression to the knee increased the sensitivity of saline load tests in the assessment of a small traumatic knee arthrotomy (open knee injury).